Sovereignty over natural resources and its implications for climate justice. (15th February 2016) - Banai, Ayelet
Abstract : In the current international system, sovereign states hold extensive rights over the natural resources in their territories. How are sovereign rights in natural resources justified? What are the implications of these rights for the demands of climate justice, which pertain to the use and management of natural resources—for example, rainforests? This article reviews five theories of territorial rights, in contemporary political and legal philosophy, and the justifications that they provide for territorial jurisdiction over natural resources. It is argued that insofar as the philosophical‐normative perspectives justify sovereigns' jurisdiction over natural resources within their borders, they also give rise to limits on the legitimate and permissible exercise of the jurisdictional prerogative. This theoretical proposition is then illustrated in the case of international climate‐justice obligations of rain‐forest‐rich countries. WIREs Clim Change 2016, 7:238–250. doi: 10.1002/wcc.383 This article is categorized under: Climate, Nature, and Ethics > Climate Change and Global Justice